Current antifungal drugs and immunotherapeutic approaches as promising strategies to treatment of fungal diseases - Sanam Nami; Ali Aghebati‐Maleki; Hamid Morovati; Leili Aghebati‐Maleki (2018)
Invasive candidiasis (IC) can affect individuals with various underlying diseases hospitalized in different parts of hospitals. In recent decades, IC has caused 27-55% mortality in general population. Although Candida albicans (C. albicans) is still the most common cause of IC, non-albicans infections such as C. krusei, C. glabrata, C. lusitaniae, C. tropicalis, and C. parapsilosis have been increased in recent years. Treatment of invasive fungal infections is challenging as the number of existing antifungals is limited and more problems include: toxicity, drug interactions, and drug resistance. These problems provide a clear rationale for the development of new immunotherapies to increase outcomes in patients with invasive fungal infections. Thus, the purpose of this paper is to complete review of the current and modern antifungal drugs in IC therapy and focus on the role of immunotherapy in preventing and controlling the disease. Therefore, we review the features of current research efforts directed towards devising safe and effective immunotherapeutic options for fungal infections, including work on antifungal vaccines, engineered T-cells, cytokines, monoclonal antibodies, and other agents.